Association between objective response rate and overall survival in metastatic neuroendocrine tumors treated with radioembolization: a systematic literature review and regression analysis. Issue 11 (1st November 2020) - Pollock, Richard F; Brennan, Victoria K; Peters, Ralph; Paprottka, Philipp M
ABSTRACT: Objectives: Neuroendocrine tumors (NETs) are a heterogeneous group of cancers arising from neuroendocrine cells. The aim was to evaluate objective response rate (ORR) as a predictor of overall survival (OS) in patients with metastatic NETs (mNETs) treated with radioembolization (RE). Methods: Randomized controlled trials and observational studies of RE treatment of mNETs were identified by systematic literature review (SLR). Pooled ORR and OS estimates were calculated and a weighted generalized linear model (GLM) of ORR as a predictor of OS was derived, stratified by ORR assessment criteria and RE type (Yttrium-90 resin or glass microspheres). Results: The SLR identified 32 observational studies. Mean ORR was 41% (95% confidence interval 38–45%). The Yttrium-90 resin and glass microsphere GLMs accounted for 59% and 57% of OS deviance, respectively. ORR was a significant predictor of OS in the resin microspheres model (p < 0.001), but not the glass microspheres model (p = 0.11). Conclusions: A weighted GLM showed a significant relationship between ORR and OS in patients with mNETs treated with Yttrium-90 resin microspheres. ORR could therefore potentially be an OS surrogate in future trials of Yttrium-90 resin microspheres. Further research is needed to confirm the relationship between ORR and OS and the difference between resin and glass microspheres.